(untitled) (Journal of Renal and Hepatic Disorders, 2021)
Acute upper gastrointestinal (UGI) bleed is an emergency requiring immediate intervention. Recent data have shown peptic ulcer disease (PUD) to be the commonest cause of UGI bleed. We aimed to evaluate all patients with UGI bleed reporting in the emergency department. A cross-sectional, observational study from a tertiary care center; evaluated all patients with UGI bleed presenting to the outpatient and emergency departments between December 2017 and December 2018. A total of 356 patients with UGI bleed were enlisted for diagnostic and therapeutic endoscopy. Variceal bleed was present in 231 (65%) [cir-rhosis 217 (61%) vs noncirrhotic 14 (4%)] patients, nonvariceal bleed was present in 93 (26%) [cirrhosis 22(6%) vs noncirrhotic 71(20%)] patients, and no cause was determined in 32 (9%) patients. Among cirrhotic patients, alcoholic liver disease (n = 172) was the most common, followed by cryptogenic cirrhosis (n = 32), and cirrhosis related to Hepatitis B (n =7) and hepatitis C virus (n =22), and AIH (n = 6). Among variceal noncirrhotic causes, noncirrhotic portal hypertension was present in 14 patients. In the noncirrhotic, nonvariceal group, causes of UGI bleed included esophagitis (n = 26), erosive gastritis (n = 9), and Mallory Weiss Tear (n = 7), followed by PUD (n = 23), carcinoma stomach (n = 3), carcinoma esophagus (n = 2), and duodenal polyp (n= 1). Nonvariceal cirrhotic patients had portal hypertensive gastropathy (n = 8), PUD (n = 5), duodenal erosions (n = 1), esophagitis (n= 7), and antral varix (n = 1). Interestingly, even in the nonvariceal group, alcohol was the underlying cause of UGI bleed in majority of the patients with esophagitis and erosive gastritis. Alcohol was the commonest cause of UGI bleed in majority of the cases with or without chronic liver disease, followed by PUD in small numbers in the emergency department.